2022
DOI: 10.20377/jfr-714
|View full text |Cite
|
Sign up to set email alerts
|

Workin' moms ain't doing so bad: Evidence on the gender gap in working hours at the outset of the COVID-19 pandemic

Abstract: Objective: In this project, we study changes in the working hours of men and women with and without children in the early phase of the COVID-19 crisis in Germany until August 2020. Background: The COVID-19 outbreak in Europe led to a sharp decrease in economic activity, along with temporary closures of childcare facilities and schools. Subsequent changes in working hours in the early phase of the pandemic and during summer 2020 may have contributed to inequalities between men and women or parents and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
3
7
1
Order By: Relevance
“…As other studies have already shown (Hipp & Bünning, 2021;Koebe et al, 2020;Knize et al, 2021), we also notice that several mothers do not work at all and also more mothers work flexibly and at home. Especially in the interviews, apparent benefits for family wellbeing becomes clear in cases where mothers can stop working for a while or significantly reduce their working hours.…”
Section: The Role Of the Mothers Is Particularly Important In Overcoming The Crisissupporting
confidence: 84%
See 1 more Smart Citation
“…As other studies have already shown (Hipp & Bünning, 2021;Koebe et al, 2020;Knize et al, 2021), we also notice that several mothers do not work at all and also more mothers work flexibly and at home. Especially in the interviews, apparent benefits for family wellbeing becomes clear in cases where mothers can stop working for a while or significantly reduce their working hours.…”
Section: The Role Of the Mothers Is Particularly Important In Overcoming The Crisissupporting
confidence: 84%
“…Under the specific circumstances of the first lockdown, fathers increased the time for child care as well as mothers did, in relative terms even more, especially fathers with less work obligations (Kohlrausch & Zucco, 2020;Kreyenfeld & Zinn, 2021). Nevertheless, mothers performed the essential share of care work in most families and were more likely to reduce working hours (Knize et al, 2021;Hipp & Bünning, 2021). The increased strain of care work is accompanied by lower satisfaction with their work, their family life, and life in general (Collins et al, 2020;Huebener et al, 2020;Möhring et al, 2021).…”
Section: Individual Resourcesmentioning
confidence: 99%
“…Concerning pandemic-related altered working conditions, more fathers reported increased working hours than mothers. Here, our sample differs from prior studies that find similar changes in parents' working hours (Knize et al 2021). In contrast to prior research (e.g., Möhring et al 2021), in our sample, more fathers than mothers (53% vs. 33%) reported having worked remotely during the first months of the pandemic.…”
Section: Measurements and Analytical Strategycontrasting
confidence: 91%
“…First, during the COVID-19 crisis, changes in employment affected partners’ availability in the household. During the early phase of the pandemic, employment decreased considerably, and women were more likely than men to reduce their working hours or lose their jobs (e.g., Andrew et al 2020; Reichelt et al 2021; see, in contrast, Knize et al 2021). Whereas unemployment or reductions in working hours have been shown to be associated with overall increases in housework time, there are important gender differences in couples’ adjustment to reduced or terminated employment (e.g., Fauser 2019; Pailhé, Solaz, and Souletie 2019; van der Lippe et al 2018): task specialization by gender becomes more pronounced, and the extra domestic work is substantially greater for unemployed women than for unemployed men.…”
Section: Covid-19 Couples’ Division Of Housework and Gender Role Atti...mentioning
confidence: 99%